2013
DOI: 10.1002/aur.1274
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Difficulties in Autism Spectrum Disorder: Implications for Implicit Contextual Learning

Abstract: It is widely accepted that we use contextual information to guide our gaze when searching for an object. People with autism spectrum disorder (ASD) also utilise contextual information in this way; yet, their visual search in tasks of this kind is much slower compared with people without ASD. The aim of the current study was to explore the reason for this by measuring eye movements. Eye movement analyses revealed that the slowing of visual search was not caused by making a greater number of fixations. Instead, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…In support of this, Goldberg et al (2002) However, heightened visual search ability has not been unanimously demonstrated. In tasks where target and distracter objects are similar and participants are able to make use of context, individuals with autism exhibit slower search performance (Barnes et al, 2008;Brown et al, 2010;Kourkoulou et al, 2013). Longer search time in such tasks was found to be driven by longer duration of fixations (Kourkoulou et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In support of this, Goldberg et al (2002) However, heightened visual search ability has not been unanimously demonstrated. In tasks where target and distracter objects are similar and participants are able to make use of context, individuals with autism exhibit slower search performance (Barnes et al, 2008;Brown et al, 2010;Kourkoulou et al, 2013). Longer search time in such tasks was found to be driven by longer duration of fixations (Kourkoulou et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In tasks where target and distracter objects are similar and participants are able to make use of context, individuals with autism exhibit slower search performance (Barnes et al, 2008;Brown et al, 2010;Kourkoulou et al, 2013). Longer search time in such tasks was found to be driven by longer duration of fixations (Kourkoulou et al, 2013). It therefore seems that overall individuals with autism tend to exhibit reduced saccadic activity when task demands are high.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After a first screening step, 29 studies were retrieved. We found five studies using the SRT task (Mostofsky et al 2000;Gordon & Stark, 2007;Brown et al 2010;Travers et al 2010), two studies using the ASRT task (Barnes et al 2008;Nemeth et al 2010), two studies using the PR task (Gidley Larson & Mostofsky, 2008;Limoges et al 2013) and five studies using the CC task (Barnes et al 2008;Brown et al 2010;Kourkoulou et al 2012Kourkoulou et al , 2013Travers et al 2013). Three more studies were found screening the references Gordon & Stark, 2007;Limoges et al 2013).…”
Section: Study Characteristicsmentioning
confidence: 95%
“…Normally, skilled readers are able to determine the meanings of most unfamiliar words as they read by exploiting the contextual cues embedded within the text and by utilising their own world knowledge to fill in the information gaps (Kourkoulou et al, 2013;leekam, 2007). However, due to the overload of information in working memory, learners with ASD experience more difficulty integrating context cues to construct word meanings because they are unable to adequately attend to the semantic content during the decoding process (Henderson et al, 2011).…”
Section: Surface-level Processingmentioning
confidence: 99%